SURVEI KONDISI FISIK PEMAIN SEPAK BOLA SMAN PLUS SUKOWONO JEMBER - Karomi, Tanzil; Sulaiman, Ahmad; Apriliyanto, Rizki (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Abstract Football is the most popular sport in the world, including in Jember Regency. The number of football schools (SSB) is one proof. Not only that, many schools have football teams through extracurricular activities including SMAN Plus Sukowono Jember. The football achievements of SMAN Plus Sukowono Jember decreased from 2022 to 2023. Tests and measurements of the physical condition of players have not been carried out in the last two years. The purpose of this study was to determine the physical condition of the cardiopulmonary endurance of SMAN Plus Sukowono Jember players using the Multistage Fitness Test (MFT). This method uses a descriptive quantitative approach using test and measurement techniques. The population of football players SMAN Plus Sukowono Jember with total sampling. However, when data collection was only 14 players because some had graduated and could not attend. The results of the MFT on 14 players of SMAN Pluis Suikowono Jeimbeir above, can be described that there are no players in the superior, very good and good categories (0%), 3 players in the sufficient category (21.4%), 5 players in the less category (35.7%), 6 players in the very less category (42.9%). Thus, none of the players are categorised as above sufficient. That is, a conclusion can be drawn based on the very poor average VO2Max of 34.9 ml/kg/min. Keywords: football; physical condition; vo2max